I'll be damned : how my young and restless life led me to America's #1 daytime drama - Braeden, Eric, 1941-; Harrison, Lindsay (New York, NY : Dey St., 2017)
"For nearly four decades, fans have welcomed the star of television's number-one daytime show, The Young and the Restless, into their living rooms. While they've come to know and love the suave Victor Newman, few truly know the man behind the character, the supremely talented Eric Braeden. I'll Be Damned is his story--a startling and uplifting true tale of war, deprivation, determination, fame, and social commitment that spans from Nazi Germany to modern Hollywood."--Book jacket flap.
Beginnings and endings -- Coming to America -- From parking cars to Broadway -- The sins of the father -- Becoming Eric Braeden -- Christian -- My ten years as a bad guy -- Meeting Victor Newman -- "I'm going to make you proud" -- "Victor! Victor! Victor!" -- The good, the bad, and the mortifying -- Titanic and The man who came back -- But I digress -- Thank you, Y&R -- In closing ... -- Appendix: Thoughts on being German ; The Gorbachev speech.
Keywords: Braeden, Eric, -- 1941-; Young and the restless (Television program); Television actors and actresses -- United States -- Biography